De la morphinée à la junkie : les visages de la droguée - Jean-Jacques Yvorel (Criminocorpus)
In the last decades of the XIXth century, the chronic poisonings in the morphine multiply. The morphinomania, name given to this piece of news "disease" by a German doctor, Edouard Levinstein, affects mainly men very often doctors or belonging in the middle medical. Nevertheless it is another representation of poisoned that is going to stand out as real archetype, and this other representation is female: it is "la Morphinée".August 29th, 1969, Martine, a 17-year-old girl, dies of a heroin overdose in the toilet of the casino of Bandol. This immediately mediatized event, is going to activate a real moral panic which convinces the politicians of the necessity to legislate. So it's a girl who embodies, in France, the problem of the drug. What are points of resemblance and the points of difference between " la Morphinée" Fin de siècle and "junkie" of the seventies?